Efektifitas Media Gamifikasi Berbasis Kahoot dalam Pemahaman dan Penguasaan Al Qur’an Hadits - Nikmatul Wafiroh; Nur Aisyah; Fharadhiesty Abdyanty Putry (Civiliza Publishing, Indonesia., 2026)
The teaching of the Qur’an and Hadith often faces challenges in the form of low student motivation and poor retention of material due to the use of conventional methods that tend to be monotonous. This study aims to analyze the effectiveness of using gamification media based on the Kahoot app in improving students’ understanding and mastery of Qur’an and Hadith material. This study employs a qualitative approach with a descriptive method to gain an in-depth understanding of the learning phenomenon. Data were collected through observation of student activities, in-depth interviews with educators and students, and documentation of the learning assessment process. The results indicate that the integration of game elements in Kahoot—such as interactive quizzes, background music, and real-time leaderboards—creates a dynamic, enjoyable, and healthily competitive classroom atmosphere. The use of this digital medium has proven effective in visualizing abstract concepts and helping students construct their own understanding of the material through interactive learning experiences. Additionally, Kahoot’s instant feedback feature helps students identify misunderstandings immediately, which ultimately improves their mastery of the material and memory retention compared to traditional lecture methods. This study concludes that Kahoot-based gamification is a highly relevant and innovative strategy for improving the quality of Al-Qur’an and Hadith education in the digital age. Teachers are advised to optimize the use of this digital tool to sustain students’ interest in learning.